2019
DOI: 10.3390/molecules24101926
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Anti-Amyloid β Effect and Main Chemical Profiles of White Tea: Comparison Against Green, Oolong and Black Tea

Abstract: White tea (WT) is one of six tea types originally derived from Fujian Province, China. White tea is known for its health-promoting properties. However, the neuroprotective and anti-aggregatory properties of WT against the hallmark toxic Alzheimer’s protein, Aβ have not been investigated. In this study, WT, green tea (GT), oolong tea (OT) and black tea (BT) were manufactured using tea leaves from the cultivar Camellia sinensis (Jin Guanyin). The protective effects of these tea extracts were then studied under o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Acute lung injury or acute respiratory distress syndrome are serious clinical complications with high morbidity and mortality. 95 A study in mice showed that treatment with EGCG improved histopathological lesions, reduced pro-inflammatory markers and improved lung regeneration capacity by improving the expression of Ki67, PCNA and Ang-1 proteins. 95…”
Section: Lung Health Effectsmentioning
confidence: 99%
“…Acute lung injury or acute respiratory distress syndrome are serious clinical complications with high morbidity and mortality. 95 A study in mice showed that treatment with EGCG improved histopathological lesions, reduced pro-inflammatory markers and improved lung regeneration capacity by improving the expression of Ki67, PCNA and Ang-1 proteins. 95…”
Section: Lung Health Effectsmentioning
confidence: 99%
“…We observed that 1 μg/mL PPE exerted a highly significant reduction in both Aβ- and α-syn-induced CCR from mitochondria (Aβ42: from 2.24 ng/mL to 0.61 ng/mL, p < 0.001; α-syn: from 2.95 ng/mL to 1.43 ng/mL, p < 0.001). The inhibition by PPE was compared to that of black tea extract (BTE) as a ‘positive control’, since BTE is a well-known anti-amyloid and neuroprotectant against both Aβ and α-syn toxicity in vitro and in vivo [ 35 , 36 , 37 ]. Indeed, PPE was similarly effective to BTE in preventing CCR, especially against Aβ ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory investigations of amyloid aggregation usually employ transmission electron microscopy to visualize the effects of inhibitors at molecular level as applied in many studies (Bermejo-Bescos et al, 2010 ; Gong et al, 2014 ; Li et al, 2019 ; Scheidt et al, 2019 ). In this study, we co-incubated the amyloid peptides with HNQ (peptide: HNQ concentration = 8:1) for 3 days and took SEM images of treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…The mesh of fibers in peptide P3 incubated with HNQ disappeared ( Figure 1B ) as has been observed in similar studies on inhibitor action of 1,4-naphthoquinones (Gill, 2014 ), quinones (Gong et al, 2014 ), and other polyphenols (Ono et al, 2003 ), and copper (Mold et al, 2013 ) on amyloid formations. Amyloid β treated with white tea also showed amorphous aggregates whereas the overall density of aggregates was less in those samples treated with other types of tea (Li et al, 2019 ). Tubular aggregates of P3 appear to have dissolved as has been observed when amyloid aggregates were treated with curcumin (Yang et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%